2096. Associations with Pneumocystis Pneumonia in Solid Organ Transplant Recipients: Impact of Posttransplant Lymphoproliferative Disorder. (15th December 2022) - Yetmar, Zachary A; Duffy, Dustin; Smith, Byron; Vikram, Holenarasipur R; Brumble, Lisa M; Limper, Andrew H; Beam, Elena
Abstract: Background: Pneumocystis jirovecii pneumonia (PCP) is a potentially deadly infection afflicting the immunocompromised population, including solid organ transplant recipients. Several risk factors have been described, including acute rejection, lymphopenia, and cytomegalovirus (CMV) infection. However, little is known regarding the risk imparted by posttransplant lymphoproliferative disorder (PTLD). Methods: We performed a nested case-control study of solid organ transplant recipients diagnosed with PCP from 2000-2020. PCP was defined as positive smear or polymerase chain reaction testing with compatible clinical symptoms and radiographic findings. Two control were matched to each case by year of first transplant, first transplanted organ, and sex. Each control had at least as much follow-up from their transplant date to their matched case's PCP diagnosis date. Multivariable conditional logistic regression was performed to analyze theorized risk factors. Results: Sixty-seven cases met inclusion criteria and were matched to 134 controls (Table 1 ). Median age was 60.9 years, and the most common transplant type was kidney (52.2%). Fourteen patients had a history of PTLD, 12 of which developed PCP. All cases of PTLD were monomorphic, 6 were EBV-positive, 9 were receiving chemotherapy at the index date, and only 1 control patient was receiving PCP prophylaxis. The cases with PTLD developed PCP a median of 85 days after PTLD diagnosis, while the two controls were diagnosed more than 1 year earlier. After adjusting for age, acute rejection requiring treatment within the last 6 months, CMV infection within 6 months, current PCP prophylaxis, and lymphopenia (lymphocyte count < 0.5 x10 9 /L) within 6 months, PTLD had a significant association with PCP (OR 14.0, 95% CI 1.7-114.5; p = .014). Lymphopenia was also associated with PCP (OR 8.2, 95% CI 3.2-20.7; p < .001), while the other factors were not. Table 1: Characteristics of 67 Solid Organ Transplant Recipients with Pneumocystis Pneumonia and 134 Matched Controls Conclusion: Diagnosis of PTLD is independently associated with subsequent PCP after adjustment for recognized risk factors. This association is likely influenced by PTLD-directed chemotherapy, particularly regimens containing rituximab. PCP prophylaxis should be initiated in solid organ transplant recipients with PTLD, particularly those undergoing active therapy, and those with severe lymphopenia. Disclosures: All Authors : No reported disclosures.